Analysis of substantive provisions of axiological science in а philosophical and pedagogical aspect - Deminskaya Larisa Alekseevna (Kharkov National Pedagogical University, 2011)
Maintenance of the axiological going is considered near professionally-pedagogical preparation of future teachers. The analysis of publications is conducted on questions of history of forming axiological science and maintenance of substantive axiological provisions. It is set that in the process of professionally-pedagogical preparation of future teachers of physical education the special value acquires forming valued orientations for creation valued attitude of teacher toward personality and health of the students. Analysis of maintenance of such concepts as « a value» and «valued orientations» will allow to provide a theoretical basis for realization of axiological approach in an educational process.